Assessment of stirrups in resisting punching shear in reinforced concrete flat slab. Issue 1 (1st January 2021) - Raafat, Ahmed; Fawzi, Ahmed; Metawei, Hala; Abdalla, Hany
ABSTRACT: Punching shear is one of the critical concerns in the design of flat slab systems. This research is conducted to investigate the effect of different parameters regarding shear reinforcement on the punching strength of flat slabs. These parameters include yield stress of stirrups, extension of stirrups from column face along slab span, slab thickness, and the shape of stirrups whether multiple leg stirrups or closed stirrups. The experimental program in this research included testing eight slab specimens with dimensions of 1200 × 1200 mm and a thickness of 160 mm and 200 mm. The results of the experimental work were compared to those estimated according to local and international building codes. The results showed that using closed stirrups greatly increased the punching capacity of flat slabs even for a thickness of 160 mm.